Comparison of the effect of passive recovery and self-myofascial release in post-match recovery in female soccer players - Oliveira Carvalho Junior, G.; Naves de Oliveira Goulart, K.; Mendonça Pimenta, E.; Laís Araújo Fortes, S.; Braga Gomes, K.; Pena Couto, B. (Journal of Human Sport & Exercise, 2024)
The self-myofascial release is often included in football training routines the day after games to help athletes recover, but its effects when performed at this time have not yet been investigated. This study aimed to investigate the effect of a myofascial self-release protocol on post-match recovery in female professional soccer players. Ten players were included in the study, and all athletes underwent two study conditions: self-myofascial release (SMFR) and passive recovery (control). The SMFR was performed on the quadriceps, adductors, hamstrings, iliotibials, gluteus, and gastrocnemius bands, lasting approximately 25 minutes, on the day after the match. The study monitored various recovery markers, including the Total Quality Recovery Scale (TQR), delayed onset muscle soreness (DOMS), mood state, BRAMS (fatigue and vigour), vertical jump, countermovement jump (CMJ), 10 and 20m sprint, and creatine kinase (CK), before the game, 24 and 48 h post-match. The results showed no significant differences between the passive recovery and SMFR for any of the variables monitored. The results of this study indicate that a single session of self-myofascial release (SMFR), performed 24 hours after a female soccer match, has comparable efficacy to passive recovery for post-match.